Combined diffusion tensor imaging and magnetic resonance spectroscopy to predict neurological outcome before transjugular intrahepatic portosystemic shunt. Issue 8 (4th September 2018) - Rudler, Marika; Weiss, Nicolas; Perlbarg, Vincent; Mallet, Maxime; Tripon, Simona; Valabregue, Romain; Marjańska, Małgorzata; Cluzel, Philippe; Galanaud, Damien; Thabut, Dominique
Summary: Background: Hepatic encephalopathy (HE) may occur after transjugular intrahepatic portosystemic shunt (TIPSS) placement. Multimodal magnetic resonance imaging (MRI), combining anatomical sequences, diffusion tensor imaging (DTI) and 1 H magnetic resonance spectroscopy, is modified in cirrhotic patients. Aims: To describe multimodal MRI images before TIPSS, to assess if TIPSS induces changes in multimodal MRI, and to find predictors of HE after TIPSS in patients with cirrhosis. Methods: Consecutive cirrhotic patients with an indication for TIPSS were prospectively screened. Diagnosis of minimal HE was performed using psychometric HE test score. Multimodal MRI was performed before and 3 months after TIPSS placement. Results: Twenty‐five consecutive patients were analysed (median age = 59, male gender 76%, median Child‐Pugh score = 8 [5‐8], MELD score = 12 [9‐17], indication for TIPSS placement: ascites/secondary prophylaxis of variceal bleeding/other 20/3/2), no HE/minimal HE/overt HE: 21/4/0. 8/25 patients developed HE after TIPSS. Before TIPSS placement, metabolite concentrations were different in patients with or without minimal HE (lower myo ‐inositol, mI, higher glutamate/glutamine), but there were no differences in DTI data. TIPSS placement induced changes in metabolite concentrations even in asymptomatic patients, but not in DTI metrics. Baseline fractional anisotropy was significantly lower in patients who developed HE after TIPSS in five regions of interest. Conclusions: TIPSS placement induced significant changes in cerebral metabolites, even in asymptomatic patients. Patients who developed HE after TIPSS displayed lower fractional anisotropy before TIPSS. Brain MRI with DTI acquisition may help selecting patients at risk of HE.